1991
DOI: 10.1097/00006123-199112000-00022
|View full text |Cite
|
Sign up to set email alerts
|

Marked growth of a cerebral arteriovenous malformation

Abstract: A case demonstrating the marked growth of an angiographically occult arteriovenous malformation is presented. A review of 58 cases in which an increase in the size of an arteriovenous malformation occurred suggested that the patient's initial age may have had an important role in such growth and that both the age and the duration of follow-up were related to the extent of growth. Follow-up neuroradiological examinations are thought to be necessary for patients who have had an episode of intracranial hemorrhage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1994
1994
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…The initial hypothesis of the congenital origin and growth tendency of AVMs is presently a matter of debate. Enlargement of AVMs or regrowth after negative postoperative angiograms argue for AVMs as dynamic lesions [6,7,8,9,11,12,13,15,26,27]. These observations are supported by several immunohistochemical studies demonstrating the involvement of angiogenic factors.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…The initial hypothesis of the congenital origin and growth tendency of AVMs is presently a matter of debate. Enlargement of AVMs or regrowth after negative postoperative angiograms argue for AVMs as dynamic lesions [6,7,8,9,11,12,13,15,26,27]. These observations are supported by several immunohistochemical studies demonstrating the involvement of angiogenic factors.…”
Section: Discussionmentioning
confidence: 92%
“…Cerebral AVMs are considered to be congenital lesions [4] and are characterized by a failure of the embryonic vascular plexus to fully differentiate and develop a mature capillary bed in the affected area. However, the de novo development and growth of AVMs [5,6,7,8,9,10] or regrowth following complete resection [11,12,13,14,15], which cannot be attributed only to the congenital pattern, have also been shown. Previous studies demonstrated an involvement of angiogenic factors in the pathogenesis of AVMs.…”
Section: Introductionmentioning
confidence: 99%